2022
DOI: 10.31083/j.jin2104116
|View full text |Cite
|
Sign up to set email alerts
|

Altered Amplitude of Low-Frequency Fluctuations and Degree Centrality in Patients with Acute Subjective Tinnitus: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Background:The difference in spontaneous brain activity between acute subjective tinnitus patients (with or without hearing loss) and control participants was explored using the amplitude of low-frequency fluctuations and degree centrality methods through resting-state functional magnetic resonance imaging. The study aimed to provide an objective basis for clinical diagnosis and pathogenesis of patients with acute subjective tinnitus. Methods: Fourteen acute subjective tinnitus (AST) patients with hearing loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Decreased fALFF values were observed in several amygdala subregions in the TPAD and TPWAD groups, including the left AB/BM and right LaD. Patients with acute subjective tinnitus have been shown to exhibit abnormal DC values in auditory and nonauditory centers, such as the limbic system, frontal lobe, cerebellum, and postcentral gyrus, suggesting that those regions play an important role in tinnitus occurrence (Chen, Fan, et al, 2022 ). Interestingly, the amygdala subregions with reduced ReHo and DC values were consistent in patients with tinnitus, including alterations in the left AB/BM and right LaD, and both ReHo and DC can be used to evaluate the stability and consistency of brain function (Lv et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased fALFF values were observed in several amygdala subregions in the TPAD and TPWAD groups, including the left AB/BM and right LaD. Patients with acute subjective tinnitus have been shown to exhibit abnormal DC values in auditory and nonauditory centers, such as the limbic system, frontal lobe, cerebellum, and postcentral gyrus, suggesting that those regions play an important role in tinnitus occurrence (Chen, Fan, et al, 2022 ). Interestingly, the amygdala subregions with reduced ReHo and DC values were consistent in patients with tinnitus, including alterations in the left AB/BM and right LaD, and both ReHo and DC can be used to evaluate the stability and consistency of brain function (Lv et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gentil et al also reported a reduction in ReHo values in the limbic system and primary auditory cortex in patients with tinnitus with perceived auditory sensations (Gentil et al, 2019). Tinnitus signals originate from the auditory system and are normally suppressed by the limbic system; however, in patients with chronic tinnitus, limbic system damage leads to a reduction or loss of suppression (Leaver et al, 2016) (Chen, Fan, et al, 2022). Interestingly, the amygdala subregions with reduced ReHo and DC values were consistent in patients with tinnitus, including alterations in the left AB/BM and right LaD, and both ReHo and DC can be used to evaluate the stability and consistency of brain function (Lv et al, 2018).…”
Section: Morphological Changes In the Amygdala Subregionsmentioning
confidence: 99%
“…Animal tinnitus models have demonstrated feedback loops between the flocculus and the auditory cortex, with cochlear damage leading to upregulation of unipolar brush cells present in the cerebellum [54][55][56]. Similarly, neuroimaging studies have detected changes in the cerebellar regions, and a study of patients undergoing cerebellopontine tumor removal have demonstrated a correlation between flocculus volumes and tinnitus severity [57,58]. However, further investigative studies are needed before definitive conclusions can be made.…”
Section: Etiology and Pathophysiologymentioning
confidence: 99%
“…This non-invasive technique provides objective and detailed data regarding spontaneous neural activity, functional connectivity, and altered brain function. Notably, rs-fMRI can investigate neural pathways associated with tinnitus and evaluate treatment efficacy 12 . Zang et al 13 introduced the use of regional homogeneity (ReHo) analysis in fMRI.…”
Section: Introductionmentioning
confidence: 99%